Really learn 100 more phrasal verbs (Oxford, 2007)
Volume 2 of the successful teach-yourself workbook on phrasal verbs. Using the same tried and tested format, this book teaches learners a further 100 essential phrasal verbs used in everyday English and gives them opportunities to practise using them in a variety of exercises. Both books together will give a sound knowledge of this tricky area of English.
Keywords: Tiếng anh,Tiếng anh,English language,English language; Cụm động từ,Bài tập, các vấn đề,Tài liệu cho người học ngoại ngữ,Textbooks for foreign speakers,Verb phrase,Problems, exercises, etc